Identification of individual bottlenose dolphins (Tursiops truncatus) emitters using a cheap wearable acoustic tag - Gallo, Alessandro; Thieffry, Aglaé; Boye, Martin; Monmasson, Kyra; Hausberger, Martine; Lemasson, Alban (Frontiers in Marine Science, 2022)
Study of animal communication and its potential social role implies associating signals to an emitter. This has been a major limitation in the study of cetacean communication as they produce sounds underwater with no distinctive behavioral signs. Different techniques have been used to identify callers, but all proved to have ethical or practical limitations. Bio-logging technology has recently provided new hopes, but tags developed so far are costly and do not allow sufficiently reliable discrimination between calls made by the tagged individual and those made by the surrounding individuals. We propose a new device developed at reasonable cost while providing reliable recordings. We tested caller identification through recordings of vocal production of a group of captive bottlenose dolphins under controlled and spontaneous contexts. Our device proved to identify callers through visual examination of sonograms and quantitative measures of amplitudes, even if tagged emitters are 0.4 m apart (regardless of body orientations). Although this device is not able to identify emitters in an entire group when all individuals are not equipped, it enables efficient exclusion of individuals who were not the caller, suggesting that identification of a caller would be reliable if all the individuals were equipped. This is to our knowledge the first description of a promising low-cost safe recording device allowing individual identification of emitters for captive dolphins. With some improvements, this device could become an interesting tool to increase our knowledge of dolphin acoustic communication.